Euro Area Policies : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
To reduce the negative effects of a bank-lending crunch on economic activity, adequate credit provision should be ensured. Further bank recapitalization, restructuring and consolidation of the banking sector, and regulatory reform decisions will reduce uncertainty. A long-lasting configuration of the euro-area's fiscal architecture can be achieved by tightly coordinated reforms of national fiscal frameworks. Substantial benefits will emanate from deepening further structural reforms. Financial sector reform in the EU is proceeding at a rapid pace, and poses challenges and opportunities for the EU.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet